Vibration-induced phenomena in bulk granular materials - Golovanevskiy, Vladimir; Arsentyev, V.; Blekhman, I.; Vasilkov, V.; Azbel, Y.; Yakimova, K. (Science Direct, 2011)
Vibration is one of the mechanisms affecting bulk granular materials behaviour in transportation and material separation efficiency in pharmaceutical, chemical, food, mineral processing and other industries. Understanding fundamentals of vibration and their influence on bulk materials handling is gaining an increasing importance in the economies of scale. However, at present there appears to be no accurate and sufficient description of various phenomena observed in a granular material affected by vibration. This paper presents a concise review of physical phenomena observed in bulk granular materials affected by vibration, taken here as mechanical oscillations of relatively low amplitude and relatively high frequency. This includes three main characteristic regimes of vibration defined as vibro-fluidisation, vibro-compaction and vibro-boiling. The analysis of other factors influencing bulk granular material behaviour under vibration including air resistance, wave effects and particle oscillations decay are also given. A new characteristic regime of vibration is introduced, defined as vibro-hovering. Description of main characteristic vibration-induced bulk granular material states combined with the analysis of other contributing factors result in a more complete classification of vibration phenomena and an improved understanding of vibration-induced bulk material behaviour. Analytical conclusions are supported by the results of experimental studies, with significant potential for improvement in material separation efficiency indicated. Prerequisite vibrational parameters for effective bulk granular material flow promotion are discussed with a specific focus on physical separation processes and optimum ranges of vibrational parameters for separation and flow promotion of dry particulate matter are recommended.